2005
DOI: 10.1143/jjap.44.7904
|View full text |Cite
|
Sign up to set email alerts
|

Materials Design for Cu Gettering by Electronic Dopants in Silicon

Abstract: In the silicon device process, there is a strong demand for eliminating copper contamination. Gettering of Cu by dopant atoms is a useful method for this purpose. In this paper, the gettering of Cu is theoretically studied. We have assessed the efficiency of gettering through the evaluation of the binding energies between Cu and electronic dopants and the dissociation energies. The calculated dissociation energies well describe the efficiency of various dopants, which have been found experimentally. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The atom configurations and binding energy E b between Cu and complexes are shown in Fig 1. 0.04 2.10 0.69 [5], and those of O with Cu (0.16eV) [3].Furthermore, we found that the binding energy of BO complexes with Cu are higher with increasing oxygen atoms. Figure 1 shows the stable atom configuration and binding energy E b between Cu and complexes.…”
Section: Ecs Transactions 16 (6) 267-272 (2008)mentioning
confidence: 69%
See 1 more Smart Citation
“…The atom configurations and binding energy E b between Cu and complexes are shown in Fig 1. 0.04 2.10 0.69 [5], and those of O with Cu (0.16eV) [3].Furthermore, we found that the binding energy of BO complexes with Cu are higher with increasing oxygen atoms. Figure 1 shows the stable atom configuration and binding energy E b between Cu and complexes.…”
Section: Ecs Transactions 16 (6) 267-272 (2008)mentioning
confidence: 69%
“…For evaluating the gettering efficiency, we have determined the dissociation energy between Cu and electronic dopants [3]. The dissociation energy E diss is the sum of the diffusion barrier E d and the binding energy E b of a TM atom and a dopant atom, E diss = E d + E b .…”
Section: Methodsmentioning
confidence: 99%
“…[3,4]. The first-principles pseudo potential method based on the local-density approximation (LDA) were used for the calculation.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted here that this interpretation should not be accepted literally. In fact, there is also an opposite case for this simple interpretation based on the Coulomb interactions [3].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation